Antimicrobial Activity of Essential Oils of Trachyspermum ammi - Wadhwa, Shailendra (International Journal of Pharmaceutical & Biological Archive, 2010)
Overuse of antibiotics has selected new strains of bacterial pathogens that are resistant to the very antibiotics used to combat them. Many plants have been used for centuries by traditional healers and may have antibacterial properties. Ajowan (Trachyspermum ammi) is one such plant, having been prescribed for digestive, respiratory, renal, dental, and many other maladies in Asian traditional medicine. Our research aim was to determine whether essential oils obtained from the plant’s fruit could inhibit growth of gram-positive bacteria and gram-negative bacteria. The essential oils were obtained using the hydrodistillation method. Our methods included a well-diffusion assay.